Characterizing Emerging Markets - Pels, Jaqueline; Kidd Tomás (Organizations and Markets in Emerging Economies, 2012)
This article looks at Emerging Markets and Low Income Sector characteristics with the scope of understanding the generalizability of the market-based approaches developed in High Income Countries. The literature review highlights that existing studies have not presented clear classifications of characterics and that current listings are partial. The article adopts and adapts the market environment theory classification and summarizes the published and documented characteristics of EM and LIS. In the process it highlights that it is necessary to distinguish between primary and secondary characteristics and that many of these characteristics overlap. Finally, it builds on the organizational theory distinction between objective and enacted environment to discuss low income sector’s emerging market environments as constraints or challenges.